Integrasi Media Digital dalam Pembelajaran Literasi Sastra Anak di Tingkat Sekolah Dasar - Septia Rizqi Nur Abni; Suyatno; Anas Ahmadi; Susi Maulida (Universitas Muhammadiyah Jember, 2024)
This study evaluates the impact of integrating digital media into literary literacy instruction in elementary schools to enhance students' literacy skills and reading motivation. This research aims to measure the effectiveness of digital media in improving literacy skills and reading motivation and to identify challenges in its implementation. The research methodology employs a mixed-methods approach, with quantitative data collected from literacy and reading motivation assessments before and after the intervention, and qualitative data obtained through interviews with teachers and students. The analysis reveals significant improvements in literacy skills (average score increased from 65.4 to 78.2) and reading motivation (average score increased from 3.2 to 4.5). While digital media enhanced student engagement, there were challenges related to technology infrastructure. The study recommends better teacher training, improved infrastructure, and ongoing evaluation to maximize the benefits of digital media in literacy instruction.